Effects of processing conditions on acrylamide levels in local tapioca chips - Noor Fadilah Mohd Bakri (2020)
Acrylamide is a toxic chemical formed when certain starchy foods are cooked or processed. Generally, the production of acrylamide in food is associated with high temperature processing (cooking) method such as frying and baking. This study was carried out to investigate the effects of such processing parameters, i.e. heating time, heating temperature and cooking method, on the level of acrylamide in local tapioca chips. Acrylamide levels in the tapioca chip samples were analysed using SPE/HPLC/UV. Results showed that heating time and temperature were positively correlated with the acrylamide levels in the tapioca chips (R2 = 0.942 and R2 = 0.8712 respectively) and the highest level was found in heating time of 15 mins (447.12 mg/kg) and heating temperature at 210 °C (882.85 mg/kg). In addition, the study also found that the method of cooking (i.e. frying with vacuum fryer), produced the lowest level of acrylamide and resulted in good acceptability product characteristics compared to other methods of cooking.